From consent to authorization - Bjørn Hofmann (Etikk i Praksis: Nordic Journal of Applied Ethics)
The turn from traditional paternalism and towards patient autonomy has made informed consent a key concept for medical ethics and health legislation. However, informed consent has been attacked for a wide range of shortcomings, both conceptually and theoretically, as well as practically. Vilhjálmur Árnason has suggested an alternative to informed consent, i.e., to give authorizations. Vilhjálmur1 has been supported by other researchers, but the authorization approach has not been elaborated in any greater detail or come to widespread use in bioethics. This article describes and discusses Vilhjálmur’s and other scholars’ approach to authorizations and reflects on why this approach deserves more attention than previously given, especially for addressing the extended challenges emerging from biological sciences generating a wide range of person-related biological entities.